Considerations for Reduction of Risk of Perioperative Stroke in Adult Patients Undergoing Cardiac and Thoracic Aortic Operations: A Scientific Statement From the American Heart Association. Issue 14 (6th October 2020) - Gaudino, Mario; Benesch, Curtis; Bakaeen, Faisal; DeAnda, Abe; Fremes, Stephen E.; Glance, Laurent; Messé, Steven R.; Pandey, Aditya; Rong, Lisa Qia
Abstract : Perioperative stroke is one of the most severe and feared complications of cardiac surgery. Based on the timing of onset and detection, perioperative stroke can be classified as intraoperative or postoperative. The pathogenesis of perioperative stroke is multifactorial, which makes prediction and prevention challenging. However, information on its incidence, mechanisms, diagnosis, and treatment can be helpful in minimizing the perioperative neurological risk for individual patients. We herein provide suggestions on preoperative, intraoperative, and postoperative strategies aimed at reducing the risk of perioperative stroke and at improving the outcomes of patients who experience a perioperative stroke.